Membangun Kebijakan Jaring Pengaman Teknologi untuk Mendorong Produktivitas Hasil Riset Indonesia - Ayurisya Dominata; Aditya Wisnu Pradana; Edi Wahjono (Universitas Slamet Riyadi, 2019)
The study motivated by complaints from a number of researchers, engineers, or those engaged in research and technology about the constraints of research productivity in Indonesia, for example there is no a kind of safety net that protects researchers when conducting technology/ product research downstreaming to the public, termed in this study as a Safety Net for Technology. This research method is descriptive qualitative, with interview, observation and documentation study data collection techniques. The results of the study concluded that the Safety Net Technology was needed to increase the productivity of research results in Indonesia. Not only that, this policy idea needs technical support for good policy implementation. Not only technological safety nets, another factor found to play an important role in the productivity of research results in Indonesia is a good research administrative system.